The Influence of Fundamental Factors on Stakeholders’ Wealth with Good Mining as A Moderation of Mining Sector in Indonesia - Sukiranto, Sukiranto; Murwaningsari, Ety; Gunawan, Juniati (Technium Social Sciences Journal, 2022)
This research investigated the influence of the company’s fundamental factors on stakeholder wealth with good mining governance (GMG) as a moderating and control variable. It also evaluated the Growth, Investment Opportunity Set (IOS), and COVID-19 in the mining sector listed on the Indonesia Stock Exchange from 2016 to 2020. The fundamental factors consist of profitability (PRO), Efficiency (TATO), Liquidity (CR), and Solvency (DER). The object of this research is the mining sector companies listed on the Indonesia Stock Exchange which publish financial statements from 2016 to 2020 obtained using the purposive sampling method. The number of samples is 41 companies with a total of 205 observations. Furthermore, panel data was conducted using an analysis tool of view 10. The results showed that efficiency has a significant positive influence on Stakeholder Wealth. Meanwhile, Profitability, Liquidity, and Solvency have a significant negative influence. The good Mining Governance (GMG) variable as a moderator is proven to strengthen the influence of profitability, liquidity, and solvency on Stakeholder Wealth, excluding efficiency.